Genetic variability potential and morphometric characteristics of five geographic populations of Oryza meyeriana (Zoll. et Mor.ex. Steud.) Baill. Found in the Philippines. (2011)
This study was conducted on 5 Philippine populations of Oryza meyeriana (Zoll. et Mor. ex. Steud.) Baill. Presently available under ex situ conservation to elucidate their phenotypic and isozyme characteristics as well as their potential genetic variability structure based on 29 morphometric characteristic and 8 isozyme systems. Morphometric characterization showed a range of phenotypic characteristics generally conforming with published taxonomic description for the species, though visually the population samples can be differentiated by provenance. The population samples were polymorphic in 5 qualitative descriptors and assume ranges of quantitative values generally conforming with published taxonomic descriptions. Zymogram patterns for Alanine aminopeptidase, Isocitrate, dehydrogenase, endopeptidase, shikimate dehydrogenase, Glutamic oxaloacetate transaminase and Phosphogluconate isomerase strongly suggest inherent substantial genetic variability among the wild populations tested with 6 isozymes being polymorphic. However, isozyme pattern was not strongly correlated with phenotypic characteristics or provenance. Cluster analysis indeed indicated within sample and between sample differences and similarities. Qualitatively, Palawan samples showed discreetly different morphotypes but share values within a common range for quantitative characters. Multi-dimensional scaling confirms the aggregation of Palawan population as well as the geographic separation of Sorsogon and Nueva Vizcaya populations. Results therefore have substantially demonstrated significant genetic diversity potential of O. meyeriana populations occurring in the Philippines. Further, phenotypic and isozyme characterization have shown that the local populations were composed of diverse morphotypes, where genetic diversity maybe expressed both between and within geographic populations. Recommendations for finer and wider analysis of genetic structure in support of developing genetically effective conservation approach for the local populations of O. meyeriana were suggested.
Keywords: Rice--Genetics.